2020
DOI: 10.1371/journal.pone.0235903
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the influencing factors of urbanization in the Xinjiang Uygur Autonomous Region over the past 27 years based on VIIRS-DNB and DMSP/OLS nightlight imageries

Abstract: The Xinjiang Uygur Autonomous Region is the core economic area of the "Silk Road Economic Belt". The urbanization of this region plays a highly important role in economic and cultural communications between China, Central Asia and Europe. However, the influencing factors of urbanization in this region remain unclear. In this study, we presented a new modified thresholding method to extract the urban built-up areas from two nightlight remote sensing data sources, i.e., the DMSP/OLS and VIIRS/DNB nightlight imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
0
12
1
Order By: Relevance
“…These showed that although most of soils were contaminated by trace elements, the pollution status does not reach harmful levels to human health. In fact, compared with other industrial developed areas in China, trace element contents in farmland soils of Xinjiang was low 1 , 7 , 21 , 29 . For example, Zn, Pb, Cr and Cd contents in farmland soils of Beijing were 81.8, 18.5, 75.7 and 0.18 mg·kg −1 , respectively 6 .…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…These showed that although most of soils were contaminated by trace elements, the pollution status does not reach harmful levels to human health. In fact, compared with other industrial developed areas in China, trace element contents in farmland soils of Xinjiang was low 1 , 7 , 21 , 29 . For example, Zn, Pb, Cr and Cd contents in farmland soils of Beijing were 81.8, 18.5, 75.7 and 0.18 mg·kg −1 , respectively 6 .…”
Section: Discussionmentioning
confidence: 80%
“…Xinjiang is located in an economically underdeveloped region in the inland northwest, China, the lower industrial and traffic conditions introduced less trace elements into the farmland soils compared with the central and eastern China 3 , 41 . In addition, most of cultivation periods in Xinjiang farmland were shorter than 30 years as major land development along with population migration was carried out after 1980s 29 , 42 . The shorter cultivation periods also resulted in fewer trace elements into farmland soils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the prevalence of high myopia for students living in northern Xinjiang was lower than that in southern Xinjiang. Due to the higher level of economic development and education in northern Xinjiang, students living in this region may have greater pressure related to studying and lower levels of outdoor activities than those living in southern Xinjiang, which may result in a higher prevalence of myopia 18,24 …”
Section: Discussionmentioning
confidence: 99%
“…The urbanization development level varies greatly between provinces in China, representing the spatial differentiation under the comprehensive effect of many factors such as economy, society, politics, and ecology within the region. However, Li [102] conducted an exploratory study on this using GeoDetector based on the night light data. He analyzed the factors affecting urbanization development in Xinjiang and pointed out that the influence of human factors is weakening, while the influence of geographical environment factors is slowly increasing, with fixed assets investment, topography index, per capita water resources, and other indicators making more contributions.…”
Section: Methodsmentioning
confidence: 99%